The Case of Skrypka as an Epitome of the Effectiveness of Constitutional Complaint in Ukraine - Терлецький, Дмитро Сергійович; Терлецький, Д. С.; Terletskyi, Dmytro S.; Негара, Родіон Віталійович; Негара, Р. В.; Nehara, Rodion V. (Academic Insights Press, 2024)
Background: The article thoroughly examines the efficacy of constitutional complaints within Ukraine, utilising the Skrypka case as a pivotal illustration. Through comprehensive scrutiny, the authors analysed factual circumstances, national legislative frameworks governing contentious legal issues, and judicial precedents pertinent to the Skrypka case. The authors’ contention revolves around the primary role of a constitutional complaint in safeguarding an individual's violated constitutional rights, concurrently serving to fortify the constitutional order of the state. Methods: To comprehensively understand the subject, the authors conducted an in-depth review of relevant court decisions, meticulously analysing the legal arguments presented by judges. Additionally, they examined the positions of knowledgeable scholars to identify and comprehend the current expert assessments and proposals. Results and Conclusions: Through an in-depth review of judicial practices, the article delineates three predominant perspectives regarding the influence of decisions emanating from Ukraine's Constitutional Court subsequent to constitutional complaint reviews on the reevaluation of conclusive court decisions in specific cases: (1) The decisions of the Constitutional Court of Ukraine cannot impact contested legal relationships because these relationships existed prior to the adoption of these decisions by the Constitutional Court of Ukraine; (2) Review under exceptional circumstances is applicable only to decisions where the claims have been fully or partially satisfied (i.e., are subject to execution) but have not yet been enforced; (3) The decisions of the Constitutional Court of Ukraine are primarily significant as rulings of a general nature, establishing legal conclusions for resolving future cases.
Terletskyi D. The Case of Skrypka as an Epitome of the Effectiveness of Constitutional Complaint in Ukraine / D. Terletskyi, R. Nehara // Access to Justice in Eastern Europe. – Academic Insights Press, 2024. – 7(2). - P. 375-392. URL: https://doi.org/10.33327/AJEE-18-7.2-n000208
Keywords: constitutional complaint; legal remedy; judicial practice; exceptional circumstances